Porous carbon material based on microwave calcination and preparation method thereof

The carbon substrate is mixed with potassium hydroxide and then calcined and post-treated by microwave calcination, which solves the problem of large grain size and difficult to regulate defects in the preparation of porous carbon materials, and achieves the preparation of porous carbon materials with high specific surface area and low energy consumption.

CN119612510APending Publication Date: 2025-03-14CHENGDU EMINENT NEW ENERGY TECH CO LTD +2
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411692620.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing porous carbon material preparation technology has problems such as large grain size, difficulty in controlling defects, and unreasonable distribution of pore volume and pore size, resulting in unsatisfactory specific surface area and high energy consumption.

Method used

The porous carbon material is prepared by microwave calcining. By mixing the carbon substrate with potassium hydroxide in a certain proportion, stirring and pressing the blank, calcining is performed in a microwave calcining furnace, and pickling and drying are performed to adjust the structure and performance of the material.

Benefits of technology

The high specific surface area, good pore structure and low energy consumption of porous carbon materials are achieved, which reduces the preparation cost of the material and improves the performance applicability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119612510A_ABST
    Figure CN119612510A_ABST
Patent Text Reader

Abstract

The invention discloses a porous carbon material based on microwave calcination and a preparation method thereof, and belongs to the field of porous carbon preparation, the preparation method comprises the steps that a carbon base material and potassium hydroxide are mixed according to the mass ratio of 1: 1-5, a mixed material is obtained, and the carbon base material comprises biomass carbon, resin carbon and fossil carbon; the mixing comprises the following steps: putting the carbon base material and potassium hydroxide into a mixer, and stirring at the rotating speed of 200-600rpm for 3-20 minutes; pressing the mixed material into a block body, and putting the block body into a microwave calcining furnace for calcining treatment; and the calcined block is subjected to acid pickling and drying treatment. The cost and the performance can be adjusted as required by using diversified raw material sources, and the trend of green chemistry and sustainable development is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of porous carbon preparation, and in particular to a porous carbon material based on microwave calcination and a preparation method thereof. Background Art

[0002] With the rapid development of negative electrode material technology for new energy batteries in the past two years, new gas-phase silicon-carbon negative electrode materials have shown better charge-discharge specific capacity and long cycle stability than traditional nano-silicon-carbon negative electrode materials, making gas-phase silicon-carbon negative electrode materials have broad market prospects. Under this wave, porous carbon, a skeleton carbon material of gas-phase silicon-carbon, has also triggered a research boom in the scientific research and industrial circles. Porous carbon materials are mainly prepared by alkali activation method and water vapor or CO2 activation method. The alkali activation method is to use strong alkali, such as NaOH or KOH, to mix with carbon-based materials in a certain proportion, and then etch under high-temperature calcination conditions. The water vapor and carbon dioxide activation method is to use biomass-based carbon in a rotary kiln at a temperature of 800~1200℃, and introduce a large amount of water vapor or carbon dioxide for etching. However, both the alkali activation method and the water vapor or carbon dioxide activation method require a large amount of protective gas and long-term high-temperature calcination treatment, which not only takes a long processing time, but also makes the porous carbon material grain size large, the defect degree difficult to control, and the pore volume, pore size, and specific surface area distribution unreasonable. It also brings about a large amount of energy consumption, and the cost of product preparation remains high.

[0003] Microwave calcination is a heat treatment method that can quickly increase the temperature of materials and is green, clean and environmentally friendly. Compared with traditional high-temperature heat treatment methods, the temperature of the heated materials is often gradually transferred from the outside to the inside of the object through the process of heat radiation, heat conduction and heat convection in traditional high-temperature sintering materials, resulting in uneven heating temperature of the materials and obvious differences in crystal defects between the internal and external materials. However, the principle of microwave heating is that the material is transmitted to the inside of the material through microwaves, so that the microwaves are coupled with the basic structure of the material to generate heat, and the material undergoes dielectric loss in the electromagnetic field and heats the material as a whole. This process allows the material to be heated more evenly, with low internal and external temperature gradients, and the material crystal structure is more stable and homogeneous. Compared with traditional high-temperature calcination methods, the materials treated with microwave calcination have smaller grain sizes, richer defects, lower energy consumption, and the prepared porous carbon materials have higher specific surface area and micropore ratio. At present, microwave high-temperature calcination has been widely used in sintering ceramic materials and superconducting materials, but has not yet been used in the field of porous carbon preparation.

[0004] Therefore, how to reduce the grain size of porous carbon materials, increase the defect degree of porous carbon materials, balance the specific surface area and micropores, and improve the absorption and conversion of energy during microwave calcination, quickly prepare porous carbon materials, and reduce energy consumption as much as possible and reduce the cost of porous carbon materials are technical problems that technical personnel in this field urgently need to solve. Summary of the invention

[0005] One of the purposes of the present invention is to provide a method for preparing porous carbon materials based on microwave calcination to solve the defects of porous carbon materials in the prior art, such as large grain size, difficult to control defect degree, and unreasonable distribution of pore volume, pore diameter and specific surface area.

[0006] The present invention is achieved through the following technical scheme. A method for preparing a porous carbon material based on microwave calcination comprises: mixing a carbon substrate with potassium hydroxide in a mass ratio of 1:1-5 to obtain a mixed material, wherein the carbon substrate comprises biomass carbon, resin carbon and fossil carbon; the mixing comprises putting the carbon substrate and potassium hydroxide into a mixer for stirring at a rotation speed of 200-600 rpm for a stirring time of 3-20 min; pressing the mixed material into a block, putting the block into a microwave calcining furnace for calcining; and pickling and drying the calcined block.

[0007] Furthermore, the biomass carbon includes one or more combinations of carbons obtained by carbonizing coconut shells, wood chips, nut shells, bamboo, bagasse, corn stalks, and cotton stalks.

[0008] Furthermore, the resin carbon includes one or more combinations of carbons obtained by carbonizing epoxy resin, phenolic resin, polyester resin, and polyamide resin.

[0009] Furthermore, fossil carbon includes one or more combinations of petroleum coke, needle coke, pitch coke, asphalt, anthracite, etc.

[0010] Furthermore, the particle size distribution of the carbon substrate is as follows: D0 is 1.0-3 μm, D10 is 3-6.0 μm, D50 is 8-15 μm, and D100 is 20-40 μm.

[0011] Furthermore, the pressure used to press the mixed material into blocks is 1.0-15.0 Mpa, the block density is 0.5-2.0 g / cm3, and the block thickness is 0.1-1.0 cm.

[0012] Furthermore, the calcination treatment includes evacuating the material filling chamber of the microwave calcination furnace, controlling the oxygen content to 50-200 ppm, setting the power of the microwave calcination furnace to 100-1400 W, heating up the microwave calcination furnace for 10-30 min, maintaining the constant temperature for 30-90 min, and cooling to room temperature after the insulation is completed.

[0013] Furthermore, the pickling and drying treatment includes soaking the calcined block in hydrochloric acid or nitric acid with a concentration of 1-10 mol / L for 1-6 hours, stirring while soaking, and the stirring speed is 100-800 rpm. After the pickling is completed, the filter cake is filtered to obtain a filter cake, and the filter cake is washed with deionized water to a pH value of 6-8. The washed filter cake is placed in a drying oven for drying at a drying temperature of 100-150°C and a drying time of 2-8 hours.

[0014] Another aspect of the present invention further provides a porous carbon material based on microwave calcination, wherein the porous carbon material is prepared according to the preparation method as described above.

[0015] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0016] 1. The porous carbon material based on microwave calcination provided by the present invention uses different types of carbon substrates, including biomass carbon, resin carbon, fossil carbon, etc. This diversified source of raw materials can not only adjust the cost and performance according to needs, but also utilize waste biomass and industrial by-products, which is in line with the trend of green chemistry and sustainable development.

[0017] 2. The present invention uses potassium hydroxide as an activator, which can effectively promote the formation of the pore structure of the carbon material. Potassium hydroxide can promote the oxidation of carbon and the generation of pores under high temperature conditions, thereby improving the specific surface area, porosity and adsorption performance of the material. The use of potassium hydroxide helps to obtain a carbon material with a good porous structure, which can be applied to fields such as batteries, supercapacitors, catalyst carriers, etc.

[0018] 3. The present invention uses microwave calcination to prepare porous carbon materials, which has the advantages of fast heating speed, concentrated energy, and uniform temperature compared to traditional heating methods. Microwave radiation can directly act on the molecules of carbon materials, making heating more efficient and shorter, thereby reducing energy consumption, and can more accurately control the temperature and time of the calcination process to obtain a more ideal material structure. The microwave calcination process can promote the precise adjustment of the pore structure of the carbon substrate. By changing the calcination temperature and time, the distribution of pore size can be controlled, thereby optimizing the material's adsorption capacity, conductivity and other properties to meet different application requirements.

[0019] 4. The present invention can remove impure substances and surface impurities through post-treatment steps such as pickling and drying, thereby improving the purity and stability of the final product. These post-treatment steps help to remove residual potassium hydroxide, acidic impurities, etc., and obtain a high-purity, highly porous carbon material. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The drawings described herein are used to provide a further understanding of the embodiments of the present invention, constitute a part of this application, and do not constitute a limitation of the embodiments of the present invention. In the drawings:

[0021] Figure 1 This is a scanning electron microscope image of the porous carbon material prepared in Example 1 of the present invention.

[0022] Figure 2 This is a nitrogen isothermal adsorption-desorption curve diagram of the porous carbon material prepared in Example 1 of the present invention.

[0023] Figure 3 This is the pore volume-pore size distribution diagram of the porous carbon material prepared in Example 1 of the present invention.

[0024] Figure 4 This is the XRD pattern of the porous carbon material prepared in Example 1 of the present invention.

[0025] Figure 5 This is the Raman image of the porous carbon material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. The components of the embodiments of the present invention described and shown in the drawings here can be arranged and designed in various different configurations. In the present invention, unless otherwise specified, the raw materials used are commercially available products well known in the art.

[0027] Embodiment 1,

[0028] This embodiment is a porous carbon material prepared by microwave calcination and a preparation method thereof. The specific implementation scheme includes the following steps:

[0029] Step 1: Weigh 20g of crushed biomass-based coconut shell charcoal, whose particle size is about D0 1.6μm, D10 3.7μm, D50 7.8μm, D100 22.5μm, marked as sample A; weigh 60g of potassium hydroxide (KOH) again, marked as sample B, place the two groups of materials in the silo of the high-speed mixer and evacuate.

[0030] Step 2: Mix the two groups of materials, sample A and sample B, evenly in a high-speed mixer. The mixer speed is 350 rpm and the mixing time is 15 minutes. After the operation is completed, take out the mixed material and mark it as sample C.

[0031] Step 3: Place the evenly mixed C sample on the mold and press it with a pressure of about 5.0Mpa. The block density is about 0.92g / cm 3 , its thickness is about 0.3cm, marked as sample D.

[0032] Step 4: Place sample D in a microwave high-temperature calcination furnace and evacuate until the oxygen content is ≤50ppm. Start the high-temperature calcination program. The microwave calcination power is 1200W. The microwave calcination heating time is 10min. The temperature is raised from room temperature of about 25℃ to 800℃. After keeping the temperature constant for 30min, it is naturally cooled until the temperature drops to ~25℃. Then take out the material and mark it as sample E.

[0033] Step 5: Take out sample E, dissolve it with deionized water, disperse it evenly in a blender at 300 rpm for 2 hours, filter it, and rinse it repeatedly with deionized water. Repeat the above steps 3 to 5 times and mark the filtered material as sample F.

[0034] Step 6: Take out sample F and rinse it with 6mol / L dilute hydrochloric acid until the pH value is around ~7, and mark it as sample G.

[0035] Step 7: Place sample G in a vacuum drying oven and dry at 120 °C for 4 hours to obtain sample H, which is a porous carbon material calcined by microwave high temperature. Its specific surface area is 1823.10 m 2 / g, pore volume 0.93 cm 3 / g, pore size 2.04nm.

[0036] Figure 1 A scanning electron microscope image of the porous carbon material prepared in this example is shown.

[0037] As can be seen from the figure, the particle morphology of the porous carbon material. The particle shape is irregular and the surface is relatively rough. These particles obviously have different sizes and morphologies, showing the porous structure characteristics of the carbon material. And it can be seen from the figure that the porous carbon material of this embodiment has a high specific surface area, good chemical stability and electrical conductivity, and can be used in electrochemical capacitors, catalyst carriers, adsorption materials and other fields.

[0038] Figure 2 The nitrogen isothermal adsorption-desorption curve image of the porous carbon material prepared by this embodiment is shown.

[0039] From the vertical axis in the figure (Quantity Adsorbed, cm³ / g STP): it represents the amount of nitrogen adsorbed by the porous carbon material per unit mass, in cubic centimeters per gram at standard temperature and pressure (cm³ / g STP). The horizontal axis represents the relative pressure, where P is the actual pressure in the adsorption measurement and P0 is the saturated vapor pressure of nitrogen at liquid nitrogen temperature. The relative pressure ranges from 0 to 1.

[0040] The adsorption-desorption curve in the figure, adsorption process: the part of the curve from the lower left corner to the gradually increasing pressure. When the relative pressure increases from 0 to 1, it means that nitrogen is gradually adsorbed to the surface and pores of the porous carbon material. Desorption process: the part of the curve from the upper right corner where the pressure gradually decreases. It means that nitrogen is gradually released from the surface and pores of the porous carbon material.

[0041] Low relative pressure area (0 to about 0.1):

[0042] In the low relative pressure section, the adsorption amount increases rapidly, which indicates that there are a large number of micropores (<2nm) in the porous carbon material. At very low relative pressure, a large amount of nitrogen can be adsorbed, indicating that the material has a microporous structure with a high specific surface area.

[0043] Medium relative pressure area (about 0.1 to 0.9):

[0044] The adsorption amount continues to increase, but the growth rate slows down. This stage usually corresponds to the filling of the mesoporous (2-50nm) structure. The presence of mesopores makes the adsorption amount increase with increasing pressure, showing the mesoporous adsorption characteristics of porous carbon materials.

[0045] High relative pressure area (0.9 to 1.0):

[0046] When the relative pressure approaches 1, the adsorption amount tends to saturation and reaches a stable value. This part of the adsorption corresponds to the filling of macropores (>50nm) and the adsorption equilibrium after the completion of multilayer adsorption.

[0047] The steep rise in the low relative pressure region indicates the presence of porous materials with high specific surface areas. The rapid rise at the beginning indicates the micropores (high surface area micropores) in the material. The slow rise and hysteresis loop in the medium and high relative pressure part indicate the presence of mesopores and some macropores.

[0048] The curve of the hysteresis loop shows obvious adsorption hysteresis, indicating that there is a complex pore structure inside the material. This phenomenon shows that it is difficult for nitrogen to escape completely under high relative pressure, suggesting that the porous carbon material contains some relatively complex pore structures.

[0049] Figure 3The pore volume-pore size distribution picture of the porous carbon material prepared by this embodiment is shown. As can be seen from the figure, the vertical axis (DV / dlog(D) Pore Volume, cm³ / g): represents the pore volume per unit mass of material within a specific pore size range, in units of cm³ / g. DV / dlog(D) represents the rate of change of pore volume, that is, the rate at which the pore volume changes with the logarithm of the pore size. Therefore, the larger its value within a certain pore size range, the larger the pore volume within the range. The horizontal axis (PoreDiameter, nm): represents the pore size, in units of nanometers (nm).

[0050] The curve in the figure is that the horizontal axis ranges from 0 to 130 nanometers, covering the pore size range from micropores (<2nm) to mesopores (2-50nm) and some macropores (>50nm). The vertical axis ranges from 0 to 1.8 cm³ / g, indicating the range of pore volume.

[0051] As can be seen from the figure, in the small pore size range (<10nm), the curve has a higher peak on the ordinate. This shows that the porous carbon material has a higher pore volume in the small pore size range (mainly micropores and some small mesopores). Especially between pore sizes of 2 and 10 nanometers, the pore volume rises rapidly to a maximum value, indicating that the material is mainly composed of micropores and small mesopores, with a large number of small pore structures.

[0052] As the pore size increases (>10nm), the curve drops rapidly and tends to be stable. This shows that within the range of larger pore sizes (>10nm), the pore volume gradually decreases. In other words, although there may be some larger pores in the sample, their contribution to the total pore volume is small.

[0053] Appearance of peak: There is an obvious peak in the pore size range of 2 to 10 nm, indicating that the micropores (<2 nm) and small mesopores (2-10 nm) in the porous carbon material partially occupy a larger pore volume.

[0054] After the pore size exceeds 10 nm, the pore volume decreases rapidly, indicating that the pores in this range contribute less. Therefore, the pore distribution of this material is mainly composed of micropores and small mesopores.

[0055] Therefore, it can be seen from the figure that the pore size of the porous carbon material in this embodiment is mainly micropores and small mesopores, with high specific surface area and developed pore structure, suitable for use as adsorbent, electrode material, catalyst carrier, etc. The high specific surface area helps to improve its performance in gas adsorption and energy storage materials. By adjusting the preparation conditions, the pore size distribution can also be adjusted to optimize its function. High micropore content is conducive to the ion absorption and release of energy storage materials, and improves the electrical performance of batteries and supercapacitors.

[0056] Figure 4The XRD pattern of the porous carbon material prepared in this embodiment is shown. Figure 4 The figure includes XRD curves of two different samples: Example 1 is red and Comparative Example 1 is black. The vertical axis (Intensity) represents the peak intensity of X-ray diffraction in arbitrary units (au). The horizontal axis (2θ) represents the diffraction angle in degrees (°), which is twice the angle between the X-ray incident angle and the diffraction angle.

[0057] The (002) peak and the (100) peak are typical diffraction peaks of carbon materials, representing specific planes in their crystal structure.

[0058] (002) peak, which is generally attributed to the stacking structure of graphite structure carbon materials. A wider (002) peak indicates that the material has amorphous carbon or a lower degree of graphitization.

[0059] The (002) peaks in both Example 1 and Comparative Example 1 exist, but their intensities and positions are slightly different.

[0060] The intensity of the (002) peak of Comparative Example 1 is higher, indicating that it may have a higher degree of order or graphitization. The intensity of the (002) peak of Example 1 is lower, indicating a lower degree of graphitization or more amorphous carbon.

[0061] (100) is usually located between 40° and 50°. This peak belongs to the plane spacing in the graphite structure carbon material, reflecting the arrangement of atoms in the plane. Both Example 1 and Comparative Example 1 have (100) peaks.

[0062] Similar to the analysis of the (002) peak, the information of the (100) peak can also explain the content of amorphous carbon and ordered carbon inside the material.

[0063] In the figure, the (002) peak and (100) peak of Example 1 (red curve) are both relatively broad and of low intensity, indicating a lower degree of graphitization and more amorphous carbon. The trend indicates that the material in Example 1 may be more suitable for applications such as porous adsorption materials, because amorphous structures generally have higher specific surface areas and richer pore structures.

[0064] Crystallinity: XRD patterns show different crystallinity of the two samples. The (002) and (100) peaks of Example 1 are relatively broad and low-intensity, indicating that its graphitization degree is low and has a high amorphous carbon content. Comparative Example 1 shows a higher crystallinity.

[0065] Application potential: Example 1 may be more suitable for applications in adsorption and energy storage materials due to its low crystallinity and high specific surface area, while Comparative Example 1 may have better electrical conductivity due to its higher crystallinity and is suitable for the field of conductive materials.

[0066] Figure 5 The Raman image of the porous carbon material prepared by this embodiment is shown. The vertical axis (Intensity) in the figure indicates the intensity of Raman scattering. The higher the intensity, the more common or stronger the corresponding vibration mode is in the sample. The horizontal axis (Raman Shift, cm⁻¹) indicates the Raman shift, which is measured in centimeters (cm⁻¹) and is the frequency difference between the excitation light and the scattered light.

[0067] In this Raman spectrum, two characteristic peaks are very obvious: D peak (~1350 cm⁻¹):

[0068] The position is around 1350 cm⁻¹. The D peak is a characteristic peak of amorphous carbon. It reflects the vibration mode of the disordered part of the carbon atom structure in the material, which is usually related to the presence of defective carbon atoms and edge states. The intensity of the D peak is related to amorphous carbon or defects. The higher the intensity, the higher the amorphous carbon content in the material or the presence of more lattice defects.

[0069] G peak (~1580 cm⁻¹):

[0070] The position is located at about 1580 cm⁻¹. The G peak represents the characteristic peak of graphite carbon, which represents the E2g optical mode in the planar hexagonal structure formed by the sp² hybrid orbital of carbon atoms. The intensity of the G peak reflects the content of ordered graphite carbon in the material. The higher the G peak intensity, the higher the content of ordered graphite carbon in the material.

[0071] By comparing the intensity ratio of the D peak and the G peak (ID / IG), the relative content of disordered carbon and ordered carbon in the carbon material can be estimated. Generally, the larger the ID / IG ratio, the higher the amorphous carbon content and the more defects; the smaller the ratio, the higher the degree of graphitization and the greater the ordered carbon content.

[0072] From the spectral characteristics in the figure, it can be seen that the D peak is relatively high, indicating that the porous carbon material contains a considerable amount of amorphous carbon and structural defects. The G peak is also clear and obvious, indicating the presence of an ordered graphite structure component. Porous carbon materials often have a mixture of amorphous carbon and graphite carbon to provide a high surface area and good conductivity.

[0073] So based on Figure 5 From the information in the Raman spectrum, it can be inferred that the porous carbon material prepared in this embodiment has a high specific surface area and is composed of a large amount of amorphous carbon and a certain amount of ordered graphite structure. Such structural characteristics enable the material to have good performance in applications such as adsorption, energy storage (such as batteries and capacitors) and catalysis. The high D peak indicates that the material may have more active sites, which is beneficial for adsorption and catalytic applications.

[0074] Embodiment 2,

[0075] The main steps of this embodiment are the same as those of embodiment 1, except that in this embodiment, carbonized phenolic resin is used as the raw material. The specific implementation scheme includes the following steps:

[0076] Step 1: Take out the phenolic resin, place it in a graphite crucible for carbonization, introduce N2 as a protective gas, and heat it from room temperature (about 25°C) to 500°C at a heating rate of 5°C / min, and keep the temperature constant for 4 hours. After naturally cooling to 25°C, the carbonized phenolic resin material is obtained, marked as sample A.

[0077] Step 2: Take out sample A and crush the carbon material after carbonization of phenolic resin with a jet mill. The particle size is approximately: D0 1.4μm, D10 3.3μm, D50 7.7μm, D100 25.6μm, marked as sample B.

[0078] Step 3: Weigh potassium hydroxide (KOH) and mix it with the carbonized and crushed phenolic resin sample B in a mass ratio of KOH: carbon = 3:1. The remaining experimental steps are carried out according to the implementation case 1. The resin-based porous carbon material can be obtained, and its specific surface area is 1768.82 m 2 / g, pore volume 0.79 cm 3 / g, pore size 2.13nm.

[0079] Embodiment 3,

[0080] The main steps of this embodiment are the same as those of embodiment 1, except that the carbon-based material used in this embodiment is asphalt, and the remaining experimental steps are the same as those of embodiment 1. The specific surface area of ​​the asphalt-based porous carbon material finally obtained is 2377.82 m 2 / g, pore volume 1.19 cm 3 / g, pore size 2.87nm.

[0081] Embodiment 4,

[0082] The main steps of this example are the same as those of Example 1, except that the carbon-based material used in this example is needle coke, and the remaining experimental steps are the same as those of Example 1. The specific surface area of ​​the needle coke porous carbon material finally obtained is 1334.5 m 2 / g, pore volume 0.67 cm 3 / g, pore size 2.21nm.

[0083] Comparative Example 1

[0084] This comparative example serves as the control group of Example 1. After selecting the raw materials and uniformly mixing them in the manner of Implementation Case 1, the mixed material is placed in a high-temperature tube furnace, and N2 is introduced as a protective gas at a heating rate of 3°C / min. The temperature is raised from room temperature of about 25°C to 800°C, and the heating time is ~260min. The temperature is kept constant for 0.5h. After naturally cooling to ~25°C, the material is taken out, and pickling and drying are performed in the manner of Example 1 to obtain the porous carbon material of this comparative example.

[0085] Comparative Example 2

[0086] This comparative example serves as a control group of Example 2. After selecting raw materials and uniformly mixing them in the manner of Implementation Case 2, high-temperature heat treatment, acid washing, and drying are performed in the manner of Comparative Example 1 to obtain the porous carbon material of this comparative example.

[0087] Comparative Example 3

[0088] This comparative example serves as a control group of Example 3. After selecting raw materials and uniformly mixing them in the manner of Implementation Case 3, the remaining operating steps are the same as those in Comparative Example 1 to obtain the porous carbon material of this comparative example.

[0089] Comparative Example 4

[0090] This comparative example serves as a control group of Example 4. After selecting raw materials and uniformly mixing them in the manner of Implementation Case 4, the remaining operating steps are the same as those in Comparative Example 1 to obtain the porous carbon material of this comparative example.

[0091] Experimental example

[0092] The porous carbon materials prepared in the above embodiments and comparative examples were statistically analyzed to obtain a porous carbon material data comparison table as shown in Table 1.

[0093] Table 1. Porous carbon material data comparison table

[0094]

[0095] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing porous carbon materials based on microwave calcination, characterized in that: The preparation method comprises: The carbon substrate and potassium hydroxide are mixed in a mass ratio of 1:1-5 to obtain a mixed material, wherein the carbon substrate includes biomass carbon, resin carbon and fossil carbon; The mixing material comprises placing the carbon substrate and potassium hydroxide into a mixer and stirring them at a stirring speed of 200 to 600 rpm for 3 to 20 minutes; The mixed material is pressed into blocks, and the blocks are placed in a microwave calcining furnace for calcining treatment; The calcined blocks are pickled and dried.

2. The method for preparing porous carbon material based on microwave calcination according to claim 1, characterized in that: The biomass carbon includes one or more of carbon obtained by carbonizing coconut shells, wood chips, nut shells, bamboo, bagasse, corn stalks and cotton stalks; The resin carbon includes one or more combinations of carbon obtained by carbonizing epoxy resin, phenolic resin, polyester resin and polyamide resin; The fossil carbon includes one or more combinations of petroleum coke, needle coke, pitch coke, asphalt, and anthracite.

3. The method for preparing porous carbon material based on microwave calcination according to claim 1, characterized in that: The particle size distribution of the carbon substrate is: D0 level is 1.0~3μm, D10 grade is 3~6.0μm, D50 grade is 8~15μm, D100 grade is 20~40μm.

4. The method for preparing porous carbon material based on microwave calcination according to claim 1, characterized in that: The pressure used to press the mixed material into a block is 1.0-15.0 Mpa, the block density is 0.5-2.0 g / cm3, and the block thickness is 0.1-1.0 cm.

5. The method for preparing porous carbon material based on microwave calcination according to claim 1, characterized in that: The calcination treatment includes: vacuuming the chamber of the microwave calcination furnace filled with materials, controlling the oxygen content to 50-200 ppm, setting the power of the microwave calcination furnace to 100-1400 W, heating up the microwave calcination furnace for 10-30 min, maintaining the constant temperature for 30-90 min, and cooling to room temperature after the insulation is completed.

6. The method for preparing porous carbon material based on microwave calcination according to claim 1, characterized in that: The pickling and drying treatment includes soaking the calcined block in hydrochloric acid or nitric acid with a concentration of 1 to 10 mol / L for 1 to 6 hours, stirring the block during soaking at a stirring speed of 100 to 800 rpm, filtering the block after pickling to obtain a filter cake, and washing the filter cake with deionized water until the pH value is 6 to 8. Place the cleaned filter cake in a drying oven for drying at a temperature of 100-150°C for 2-8 hours.

7. A porous carbon material based on microwave calcination, characterized in that: The porous carbon material is prepared according to the preparation method according to any one of claims 1 to 6.

Citation Information

Cited By

  • Production process of porous carbonaceous material for solid-state battery

    CN120829160A